A post second grade comparison of achievement between students receiving beginning reading instruction in initial teaching alphabet and traditional orthography - Schenkat, Randolph Jon (My University, 1972)
The purpose of this study was to make a post second grade comparison of achievement between students receiving beginning reading instruction in i.t.a. and T.O. The experimental group was made up of 138 students who had received first grade instruction using the Early-to-Read i/t/a series during the two academic years 1968-69 and 1969-70. They had continued in the La Crosse Public Schools and had taken the Iowa Tests of Basic Skills (I.T.B.S.) at the beginning of third grade. The same number of students who received beginning reading instruction in the Ginn Series were selected for a control group. The two groups were matched by means of: 1) Ginn Pre-Reading Test given at the beginning of first grade, 2) sex and 3) socio-economic factors. In comparing the achievement of the two groups, four measures of achievement were used: I.T.B.S. Reading, Spelling, Vocabulary, and Arithmetic scores. The scores of the two groups were classified according to three ability levels; high, medium, and low; by using the Ginn Pre-Reading Test results. An analysis of variance on the four measures of achievement was conducted. In addition, an analysis of variance was done using the means of the i.t.a. and T.O. groups on the Lorge-Thorndike I.Q. Test which was given concurrently with the I.T.B.S. Correlations were also obtained between Reading and I.Q., Reading and Pre-Reading level, Pre-Reading level and I.Q., and Vocabulary and I.Q. No significant differences were found between the groups on the I.T.B.S. Reading, Spelling, or Arithmetic, however, the i.t.a. group was significantly higher on the I.Q. test and the I.T.B.S. Vocabulary test. Regardless of method, girls performed at a significantly higher level on the I.Q. test and the I.T.B.S. Reading and Spelling tests. Neither method demonstrated more effectiveness with any particular ability level. A post hoc examination revealed a more perfect I.Q. matching might have resulted in lower results for i.t.a. students in this sample. The findings indicate that i.t.a. reading instruction did not produce the superior results that its adherents purport. However, study limitations have to be considered: sensitivity of measuring instruments, difference in teaching materials, lack on control over second grade T.O. instruction, and teacher differences.
Keywords: Initial teaching alphabet; Reading (Elementary)